Decoys and Regulatory “Receptors” of the IL-1/Toll-Like Receptor Superfamily - Garlanda, Cecilia; Riva, Federica; Bonavita, Eduardo; Gentile, Stefania; Mantovani, Alberto (Frontiers in Immunology, 2013)
Members of the IL-1 family play a key role in innate and adaptive immunity and in the pathogenesis of diverse diseases. Members of IL-1R like receptor (ILR) family include signalling molecules and negative regulators. The latter include decoy receptors (IL-1RII; IL-18BP) and "receptors" with regulatory function (TIR8/SIGIRR; IL-1RAcPb; DIGIRR). Structural considerations suggest that also TIGIRR-1 and IL-1RAPL may have regulatory function. The presence of multiple pathways of negative regulation of members of the IL-1/IL-1R family emphasizes the need for a tight control of members of this fundamental system.